Differentiated Learning Models for Students with Dyslexia: A Study of Three Films Portraying Dyslexia - Darmasari, Nindi Muliasa; Rahmawati, Laili Etika (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe and explore the differentiated learning model depicted in the film Like Stars on Earth and to examine how differentiated learning types are implemented within it’s educational context. The urgency of this research lies in the importance of applying differentiated learning models to students with dyslexia, as depicted in Like Stars on Earth, to understand their learning processes, academic development, and emotional growth. Furthermore, the study highlights how teachers can create an equitable, engaging, and supportive learning environment for such students. This research employs a qualitative descriptive approach using content analysis methods. Data were collected through processes of reduction, narrative data presentation, and conclusion drawing. The data sources consist of secondary data obtained from the film Like Stars on Earth and primary data derived from books and academic journals. The findings indicate that the film Like Stars on Earth illustrates how to design lesson plans and implement several types of differentiated learning, namely content differentiation, product differentiation, and learning environment differentiation. In conclusion, the film demonstrates various learning styles of students and provides insights into appropriate follow-up actions and evaluations for learners with dyslexia.